FORMULASI SUSPENSI KERING KOMBINASI EKSTRAK ETANOL KUNYIT (Curcuma longa L.) DAN SERBUK DAGING BUAH PISANG KEPOK (Musa balbisiana Colla.) DENGAN VARIASI BAHAN PENSUSPENSI - Nurlina, Nurlina; Tomagola, M. Ilham; Hasyim, Nursiah; Rahman, Fadjaruddin (Jurnal Ilmiah As-Syifaa, 2014)
Background :For long time ago various research has been done on both curcuma and banana fruit. Result showed that curcumin which contained in curcuma and cytoindosin, tannin, amylum on banana function as antipeptic ulcer. PUD (peptic ulcer disease) is remain the most common disease of gastrointestinal tract, so which influence life quality, disorder in works, and higher of medical treatment cost. Most of patient of which expect prompt effect of preparations. Based on this, suspension was made to give the prompt effect, due to fine particles of the suspensoid which is not degradated or aggregated in time.The Aim :to obtain dry suspension from which is pharmaceutically stable from combination of curcuma (Curcuma longa L.) aethanolic extracts and the powder of banana (Musa balbisiana Colla.) flesh using a various of suspending agent.Method : it was experimental method which was a research method in laboratory conducted by preparing some formulation designs of dry suspension fromcombination of curcuma (Curcuma longa L.) aethanolic extracts and the powder of banana (Musa balbisiana Colla.) flesh.Conclusion :the suspending agent producing the pharmaceutically stable dry suspension is magnesium aluminium silicate with 4% concentration Keyword : Curcuma, Banana Fruit, Dry Suspension, Peptic Ulcer.